(untitled) (Milan Law Review, 2022)
Before The Hague Convention was signed (on 1st July 1985), it was not allowed to refer to any trust country’s law as a framework for domestic trusts having no international objective elements. The Hague Convention has instead allowed it, but it has also enabled its signatory Member Countries to outlaw any reference to such a framework (art. 13 The Hague Convention).Well, shortly after The Hague Convention came into force, Italy has instead largely acknowledged the legitimacy of domestic trusts, while extensively enforcing some domestic rules deemed to be binding under articles 15 and 18 of the Hague Convention. France’s and Germany’s approach have been different. France has ratified the Convention, but it has also enacted a trust-related law regulating any domestic fiduciary transactions (Act dated 19th February 2007. De la fiducie). Germany (which has not ratified The Hague Convention) has drawn up specific rules about fiduciary transactions, giving rise to an increasingly clear development over the last twenty years. Therefore, three different solutions to the same substantial problems in major Civil-law Countries. This essay outlines and focuses on the development of the German system.